The State of Writing on the Canadian Welfare State: What's Class Got to Do With It? - Finkel, Alvin (Labour / Le Travail, 2004)
The article analyzes scholarly works on the Canadian welfare state since 1979. Works discussed include Dennis Guest's "The Emergence of Social Security in Canada" (1979; 3rd edition, 1997), Jane Ursel's "Private Lives, Public Policy: 100 Years of State Intervention in the Family" (1992), James Struthers' '"The Limits of Affluence: Welfare in Ontario, 1920-1970" (1994), Penny Bryden's "Planners and Politicians: Liberal Politics and Social Policy, 1957-1968" (1997), and Nancy Christie's "Engendering the State: Family, Work, and Welfare in Canada" (2000). Concludes that while there has been important work in a number of areas, "the tendency in the historical and sociological literature to pay more attention to discourse than to political economy has tended to understate class dimensions in the formation of social policy."